Improved patient safety with a simplified operating room to pediatric intensive care unit handover tool (PATHQS) - Subramonian, D.; Krahn, G.; Wlodarczak, J.; Lamb, L.; Malherbe, S.; Skarsgard, E.; Patel, M. (Frontiers in Pediatrics, 2024)
Introduction: Patient handover is a crucial transition requiring a high level of coordination and communication. In the BC Children's Hospital (BCCH) Pediatric Intensive Care Unit (PICU), 10 adverse events stemming from issues that should have been addressed at Operating Room (OR) to PICU handover were reported into the patient safety learning system (PSLS) within one year. We aimed to undertake a quality improvement project to increase adherence to a standardized OR to PICU handover process to 100% within a 6-month time frame. In doing so, the secondary aim was to reduce adverse events by 50% within the same 6 months period.The model for improvement and a Plan, Do, Study, Act method of quality improvement was used in this project. The adverse events were reviewed to identify root causes. The findings were reviewed by a multidisciplinary inter-departmental group comprised of members from surgery, anesthesia and intensive care. Issues were batched into themes to address the most problematic parts of handover that were contributing to risk.Intervention: A bedside education campaign was initiated to familiarize the team with an existing handover standard. The project team then formulated a new simplified visual handover tool with the mnemonic "PATHQS'' where each letter denoted a step addressing a theme that had been noted in the pre-intervention work as contributing to adverse events. This is a provisional file, not the final typeset article Results: Adherence to standardized handover at 6 months improved from 69% to 92%. This improvement was sustained at twelve months and 3 years after the introduction of PATHQs.Additionally, there were zero PSLS events relating to handover at 6-and 12-months, with only one filed by 36 months. Notably, staff self-report of safety concerns during handover reduced from 69% to 13% at 6 months and 0 at 3 years. The PATHQS tool created in this work also spread to 6 other units within the hospital as well as to one adult teaching hospital.A simplified handover tool built collaboratively between departments can improve the quality and adherence of OR to PICU handover and improve patient safety. Simplification makes it adaptable and applicable in many different healthcare settings.